Intraoperative Acetabular Fracture - Hipfl, Christian; Perka, Carsten (The Journal of Hip Surgery, 2024)
Intraoperative acetabular fracture is a rare complication in total hip arthroplasty. It occurs mainly as a result of impaction of a cementless press-fit cup. Risk factors include decreased bone quality, highly sclerotic bone, and a press-fit that was relatively too large. The timing of the diagnosis determines the therapeutic approach. Fractures detected intraoperatively should be treated with appropriate stabilisation. Postoperatively, the stability of the implants as well as the fracture pattern determine whether a conservative treatment is initially feasible. Most acetabular fractures diagnosed intraoperatively are to be treated with a multi-hole cup, with additional screws anchoring in the different acetabular regions. In cases of large posterior wall fragments or pelvic discontinuity, plate osteosynthesis of the posterior column is indicated. Alternatively, cup-cage reconstruction can be utilised. Especially in elderly patients, the therapeutic goal must be rapid mobilisation through adequate primary stability, in order to minimise the risk of complications, revision, and mortality.
Keywords: total hip arthroplasty; complications; intraoperative acetabular fracture; periprosthetic fracture; cup revision